Information Revelation in Merger Waves - Moran, Pablo (The Review of Corporate Finance Studies, 2017)
This paper examines the hypothesis that, during merger waves, a bidder’s actions provide information for other bidders and the market. I develop a real options model to explore the interplay between acquisition timing and the market reaction to these events. The model predicts a pattern of declining announcement returns along the merger wave and various forms of contagion returns. Consistent with the model’s predictions, in a sample of U.S. mergers, I find that the dispersion in bidders’ post-acquisition performance declines along the merger wave and that the start of a merger wave is associated with an increase in the conditional correlation of a bidder’s stock returns and the stock returns of other bidders. Received February 2, 2013; editorial decision March 1, 2017 by Editor Paolo Fulghieri.